2018
DOI: 10.1002/pbc.27351
|View full text |Cite
|
Sign up to set email alerts
|

Carboplatin and vincristine neurotoxicity in the treatment of pediatric low‐grade gliomas

Abstract: In our study, neurotoxicity with vincristine occurred two times more frequently than in previously published literature. Careful neurological assessment is important to detect neurotoxicity, especially during induction. The high incidence of neurotoxicity should be considered when selecting a chemotherapy regimen for pediatric LGG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…It usually starts after a few administrations and symptoms often reside several months after treatment cessation [1,2]. VIPN can lead to suboptimal treatment due to dose reductions or omissions of VCR [10,13]. VIPN is dose-dependent, with single administration doses exceeding 2.0 mg/m 2 leading to intolerable VIPN in children [14].…”
Section: Introductionmentioning
confidence: 99%
“…It usually starts after a few administrations and symptoms often reside several months after treatment cessation [1,2]. VIPN can lead to suboptimal treatment due to dose reductions or omissions of VCR [10,13]. VIPN is dose-dependent, with single administration doses exceeding 2.0 mg/m 2 leading to intolerable VIPN in children [14].…”
Section: Introductionmentioning
confidence: 99%
“…In their retrospective study among children with low-grade gliomas treated with carboplatin and vincristine, Rosca et al demonstrated that VIPN is more developed during the induction phase, when the administrations of vincristine are more closely, suggesting an association between the increased risk of VIPN and the intensity of vincristine infusion [ 57 ]. Regarding the duration of vincristine administration, currently, bolus injections over 1–5 min are the standard for pediatric protocols.…”
Section: Treatment-related Risk Factors For Vipnmentioning
confidence: 99%
“…Children with recurrent tumors, radiographic growth of remaining tumors, or tumors in unfavorable locations inaccessible to future surgery, are advised to undergo adjuvant treatment [35]. Chemotherapy is the first-line adjuvant therapy and preferred over radiotherapy (RT) [35,57,58]. Few trials regarding different chemotherapy regiments exist [35,51,52,57,59,60] (Table 2).…”
Section: Adjuvant Therapymentioning
confidence: 99%
“…Chemotherapy is the first-line adjuvant therapy and preferred over radiotherapy (RT) [35,57,58]. Few trials regarding different chemotherapy regiments exist [35,51,52,57,59,60] (Table 2). Children with neurofibromatosis type 1 (NF-1) and associated pLGG showed a much higher response to chemotherapy (carboplatin, vincristine) with a PFS of 69% compared to 39% for the remaining pLGG [61].…”
Section: Adjuvant Therapymentioning
confidence: 99%